Dynamic Response of a Road Bridge Subjected to Passing a Heavy Vehicle over a Standard Irregularity - Numerical Modelling and Experimental Testing - Moravcik, Milan (Communications - Scientific Letters of the University of Zilina, 2022)
The paper presents an analysis of an actual problem related to dynamic effects to road bridges due to travelling a heavy vehicle over the bridge. Numerical simulations of the dynamic response are applied on a fictitious simple beam of the length Lb = 52 m with an artificial irregularity at mid-span, corresponding to a characteristic span L(b5) = 52 m of the ten-span continuous box girder bridge. A heavy four-axle truck mv = 32 t is used for dynamic excitation, travelling over the bridge at passing speed of 70 km / h. The obtained results are compared to results of the experimentally tested ten-span continuous pre-stressed reinforced concrete girder bridge at the same speed.
Keywords: dynamic bridge deflection; moving vehicle load; modal superposition; numerical simulation; dynamic testing